Effect of maturity on phenolics (phenolic acids and flavonoids) profile of strawberry cultivars and mulberry species from Pakistan - Mahmood, Tahir; Anwar, Farooq; Abbas, Mateen; Saari, Nazamid (MDPI, 2012)
In this study, we investigated how the extent of ripeness affects the yield of extract, total phenolics, total flavonoids, individual flavonols and phenolic acids in strawberry and mulberry cultivars from Pakistan. In strawberry, the yield of extract (%), total phenolics (TPC) and total flavonoids (TFC) ranged from 8.5–53.3%, 491–1884 mg gallic acid equivalents (GAE)/100 g DW and 83–327 mg catechin equivalents (CE)/100 g DW, respectively. For the different species of mulberry the yield of extract (%), total phenolics and total flavonoids of 6.9–54.0%, 201–2287 mg GAE/100 g DW and 110–1021 mg CE/100 g DW, respectively, varied significantly as fruit maturity progressed. The amounts of individual flavonols and phenolic acid in selected berry fruits were analyzed by RP-HPLC. Among the flavonols, the content of myricetin was found to be high in Morus alba (88 mg/100 g DW), the amount of quercetin as high in Morus laevigata (145 mg/100 g DW) while kaempferol was highest in the Korona strawberry (98 mg/100 g DW) at fully ripened stage. Of the six phenolic acids detected, p-hydroxybenzoic and p-coumaric acid were the major compounds in the strawberry. M. laevigata and M. nigra contained p-coumaric acid and vanillic acid while M. macroura and M. alba contained p-hydroxy-benzoic acid and chlorogenic acid as the major phenolic acids. Overall, a trend to an increase in the percentage of extraction yield, TPC, TFC, flavonols and phenolic acids was observed as maturity progressed from un-ripened to fully-ripened stages.